2017
DOI: 10.1111/jfs.12425
|View full text |Cite
|
Sign up to set email alerts
|

Serological and molecular detection of Toxoplasma gondii in sheep and goats in Kashan, Central Iran

Abstract: Toxoplasmosis is one of the most common meat‐borne parasitic infections worldwide. Consumption of raw or undercooked meat which contains Toxoplasma gondii tissue cysts is an important route of human infection. In this study, we investigate the serological and molecular prevalence of T. gondii infection in sheep and goat samples in Kashan, Iran, from 2015 to 2016. Serological (IgG antibody) and molecular detections were performed by the enzyme‐linked immunosorbent assay and polymerase chain reaction on the sera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
15
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 34 publications
6
15
3
Order By: Relevance
“…An earlier epidemiological study with geographical conditions similar to that in the present study has demonstrated that the T. gondii -IgG antibody was detected in 12.2% of the sheep and 4.4% of the goat samples in Kashan, Iran (Rasti et al 2017 ). The main seroprevalence studies reported in Iran are summarized in Table 1 .…”
Section: Introductionsupporting
confidence: 78%
See 2 more Smart Citations
“…An earlier epidemiological study with geographical conditions similar to that in the present study has demonstrated that the T. gondii -IgG antibody was detected in 12.2% of the sheep and 4.4% of the goat samples in Kashan, Iran (Rasti et al 2017 ). The main seroprevalence studies reported in Iran are summarized in Table 1 .…”
Section: Introductionsupporting
confidence: 78%
“…Antibodies were found in 30% of goats and 35% of sheep. In other investigations using ELISA, anti- T. gondii IgG was detected in 12.2% of sheep and 4.4% of goat sera samples in Kashan, Iran (Rasti et al 2017 ). Based on the results of liver juice serology, 32.6% and 48% of sheep and goats, respectively, showed antibodies against T. gondii (Bahrami et al 2019 ).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Zero prevalence toxoplasmosis in local eggs in one of the areas of this study (Haji Abad) with Warm and dry weather indicates the effect of moisture on the survival of oocyte. Across the globe, the prevalence of toxoplasmosis is high in tropical wet areas and down in warm and dry areas (Meerburg & Kijlstra, 2009;Rasti, Marandi, Abdoli, Delavari, & Mousavi, 2018). In our study, all of the isolates detected from egg were type III, our isolates from egg were similar to those of the chickens from Iran (Zia-Ali et al, 2007) and Egypt, That were mostly of type III (Dubey et al, 2003).…”
Section: Discussionsupporting
confidence: 62%
“…Zero prevalence toxoplasmosis in local eggs in one of the areas of this study (Haji Abad) with Warm and dry weather indicates the effect of moisture on the survival of oocyte. Across the globe, the prevalence of toxoplasmosis is high in tropical wet areas and down in warm and dry areas (Meerburg & Kijlstra, ; Rasti, Marandi, Abdoli, Delavari, & Mousavi, ). The high prevalence of toxoplasmosis in tropical countries in South America and Africa shows the impact of humidity on oocyte survival (Robert‐Gangneux & Dardé, ) as it increases with increasing moisture in temperate regions such as France (Afonso, Thulliez, & Gilot‐Fromont, ).…”
Section: Discussionmentioning
confidence: 99%